2016
DOI: 10.1016/j.ophtha.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy Can Improve Long-Term Visual Function in Glaucoma

Abstract: The results show that trabeculectomy slows the rate of perimetric decay and provide evidence of sustained, long-term improvement of visual function in glaucoma. These findings suggest the possibility of reversal of glaucomatous dysfunction of retinal ganglion cells and their central projections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 47 publications
(22 reference statements)
2
61
0
1
Order By: Relevance
“…In eyes with progressive normal tension glaucoma, Iverson et al 7 and Shigeeda et al 8 reported mean postoperative MD change of −0.25 dB/year and −0.44 dB/year respectively, compared with −1.05 dB/year preoperatively in both cohorts. In a recent study by Caprioli et al ,10 the mean decay rate (measured by the VF index) in patients who underwent trabeculectomy slowed from −2.4±9.3%/year preoperatively to −0.6±13.1% after surgery.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In eyes with progressive normal tension glaucoma, Iverson et al 7 and Shigeeda et al 8 reported mean postoperative MD change of −0.25 dB/year and −0.44 dB/year respectively, compared with −1.05 dB/year preoperatively in both cohorts. In a recent study by Caprioli et al ,10 the mean decay rate (measured by the VF index) in patients who underwent trabeculectomy slowed from −2.4±9.3%/year preoperatively to −0.6±13.1% after surgery.…”
Section: Discussionmentioning
confidence: 90%
“…In order to avoid the possibility of a regression to the mean effect, we compared our rates of progression post surgery with a control group matched by baseline MD and composed of patients who were treated medically, without ever having glaucoma surgery. A similar approach was used by Caprioli et al 10 in a recently published manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we focused on IOP reduction but not on restoration or improved visual function. A recent study by Caprioli et al indicated that trabeculectomy might reverse the glaucomatous dysfunction of retinal ganglion cells and their central projections [44].…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal is to slow or stop structural and functional progression while maintaining or enhancing overall quality of life. Some recent evidence also suggests that VF improvement may be achieved with IOP lowering [77]. The treating ophthalmologists should strive to maintain the IOP in a stable range to prevent further damage of the optic nerve [78].…”
Section: Treatment Goalsmentioning
confidence: 99%